2008
DOI: 10.3402/ljm.v4i3.4824
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Inflammatory Response in Trauma /Hemorrhage and Traumatic Brain Injury: Current State and Emerging Prospects

Abstract: Abstract; Traumatic injury/hemorrhagic shock (T/HS) elicits an acute inflammatory response that may result in death. Inflammation describes a coordinated series of molecular, cellular, tissue, organ, and systemic responses that drive the pathology of various diseases including T/HS and traumatic brain injury (TBI). Inflammation is a finely tuned, dynamic, highly-regulated process that is not inherently detrimental, but rather required for immune surveillance, optimal post-injury tissue repair, and regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 159 publications
2
16
0
Order By: Relevance
“…In addition, certain stress activated protein kinases or other upstream signaling enzymes can also activate the redox sensitive transcription factors such as NF-jB, AP-1 and NRF-2 thereby up regulating the synthesis of early response genes to tolerate or survive the subsequent oxidative injury. In our present study too there is an increased expression of TNF-a in mid brain region after aluminium treatment an observation similar to this, TNF-a levels are increased in the CNS after damage due to traumatic injury, ischemia, infections or diseases that involve brain degeneration, playing an important role in the adaptive response to these conditions indicating the inflammatory response [30]. Several authors have also shown the increased inflammatory response in experimental models of aluminium [31].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, certain stress activated protein kinases or other upstream signaling enzymes can also activate the redox sensitive transcription factors such as NF-jB, AP-1 and NRF-2 thereby up regulating the synthesis of early response genes to tolerate or survive the subsequent oxidative injury. In our present study too there is an increased expression of TNF-a in mid brain region after aluminium treatment an observation similar to this, TNF-a levels are increased in the CNS after damage due to traumatic injury, ischemia, infections or diseases that involve brain degeneration, playing an important role in the adaptive response to these conditions indicating the inflammatory response [30]. Several authors have also shown the increased inflammatory response in experimental models of aluminium [31].…”
Section: Discussionsupporting
confidence: 90%
“…2,3 While the acute immediate response is relatively limited in space to the immediate area of impact, the secondary response can be remote from the impact due to the action of cytokines, chemokines and damage-associated molecular pathways (DAMPs), secreted immune activators that contribute to the induction of cellular injury cascades in a paracrine or endocrine fashion. 4,5 Mitochondrial dysfunction is a prominent feature of the cellular injury response in this second phase of TBI and is linked to broad changes in cell and tissue structure and function, contributing to neurological deficits. 6 Mitochondrial dysfunction involves increased reactive oxygen species (ROS) production, calcium dysregulation, initiation of the mitochondrial permeability transition and, if mitochondrial injury is sufficiently severe, initiation of apoptosis, cell death and loss.…”
Section: Introductionmentioning
confidence: 99%
“…These danger signals function in part by activating antigen‐presenting cells, making them express co‐stimulatory molecules necessary for T‐cell activation . It has therefore been hypothesized that the reason for a higher inhibitor risk following on‐demand treatment could partly be explained by danger signals generated during a bleed and the accompanying inflammation where different cytokines, degradation products and intracellular components are released and augment the immune response to therapeutic FVIII.…”
Section: Introductionmentioning
confidence: 99%